Autoimmune diseases during treatment with immunomodulatory drugs in multiple myeloma: selective occurrence after lenalidomide. Issue 9 (September 2014) - Montefusco, Vittorio; Galli, Monica; Spina, Francesco; Stefanoni, Paola; Mussetti, Alberto; Perrone, Giulia; De Philippis, Chiara; Dalto, Serena; Maura, Francesco; Bonini, Chiara; Rezzonico, Francesca; Pennisi, Martina; et al.
Abstract Immunomodulatory drugs (IMiDs) may favor autoimmune disease (AD) occurrence. We conducted a retrospective study to evaluate AD occurrence among IMiD-treated patients with myeloma. Patients were grouped into three classes depending on the type of IMiD engaged. The first group included patients treated with thalidomide (Thal) (n = 474), the second group with lenalidomide (Len) (n = 140) and patients in the third group were first treated with Thal followed by Len (Thal-Len) (n = 94). Absolute risk of AD was 0.4% for patients treated with Thal, 4.3% for Len and 1.1% for Thal-Len. ADs manifested prevalently as autoimmune cytopenias (55%), although we observed one vasculitis, one optic neuritis, one Graves' disease and one polymyositis. ADs occurred preferentially in the first months of IMiD treatment. A previous autologous transplant was shown to be a significant risk factor. All ADs were managed with IMiD discontinuation and steroids, resolving in a few weeks, except for Graves' disease and polymyositis.